FINANCIAL METHODS OF INFLUENCE ON INNOVATIVE MODERNIZATION OF ECONOMY IN THE CONTEXT OF THE WORLD EXPERIENCE - Bilyk, R. S. (Навчально-науковий інститут міжнародних відносин КНУ імені Тараса Шевченка, 2019)
These article is about the objective preconditions and regularities of conducting transformational changes in the economy of different countries of the world on innovative basis. It is substantiated, that the development of innovative modernization of theActual problems of international relations. Release 139. 2019116economy should be one of the main means system of state regulation itself. The experience of developed countries of the world had analyzed with regard to the use of financial methods and tools for activating innovation and conducting R & D. It substantiated, that the necessity of implementation of this experience in Ukraine in order to ensure modernization of the economy through introduction of various tax privileges, accelerated depreciation of fixed capital, cheap loans, etc.. It had proved, that the development and implementation of financial regulation methods in the mechanism of innovation modernization of the economy should take into account the features and structure of the domestic economy, the depth of globalization transformations and the degree of development of financial institutions. The focus of financial regulatory methods for modernizing the economy involves the concentration, distribution and redistribution of financial and economic resources, reorientation of the economy towards an innovative model of development. The priority directions had determined and recommendations had developed on improving the institutional foundations of financial policy in the context of innovative modernization of the Ukrainian economy. Among the most important areas are the following: the search for new sources and increase of financing of innovative development, improvement of the effectiveness of the influence of financial instruments on the rate of economic growth, the growth of the share of high-tech component of the economy, etc.Key words: innovative activity, financial methods of regulation, institutional provision, innovative modernization. References1. Tsyganov S.A., Sizonenko V.O. Innovative modernisation of economy as basis of realization of national economic interests / S.A. Tsyganov, V.O. Sizonenko // Announcer of the Dnepropetrovsk university. Series are «Management of innovations», 2015. – Producing 4. – P. 101-108.2. Valinkeviich N.V. Conceptual bases of introduction of economic modernisation of enterprises in the market conditions of menage / N.V. Valinkeviich // Economic chasopis – ХХІ, 2013. – №1 (45). – P. 61-63.3. Reshetylo V.P. Tthe Global calls of structural modernisation of economy of Ukraine / V.P. Reshetylo, І.А. Ostrovskiy // The Global and national problems of economy the Mykolaiv national university of the name of V.О. Suhomlynskiy. – Producing 23, 2018. – P. 38-43.4. Luyhovets O.O. Sources of theory of modernisation and her place in economic science /O. O. Luyhovets // Investments: practice and experience, 2013. – № 10. – P. 34-36. 5. European Business Association. Available at: http://eba.com.ua.6. Geets V. Modernisation in the system «company-state-economy» / V. Geets // The European economy of Ukraine. – 2014. – №2. – . 111-124.7. Andriychuk U.A. Problems of government control of innovative activity in Ukraine / U.A. Andriychuk // Announcer of the National university «Lviv politehnika». – 2013. – Producing 776. – P. 340-346.8. Financial providing of innovative development of Ukraine : monograph / by red. М.І. Diba, О.М. Yrkevich. – К.: KNEU, 2013. – 425 p.9. Zatonatska T.G. Financing of scientifically-technological sphere by state-private partnership / T.G. Zatonatska // Scientific works of NDFI. – 2014. – № 1 (66) – P. 3-11.10. Kolodizev O.M. Methodological principles of the financial providing of management innovative development of economy: monograph / O.M. Kolodizev – H.: VD INZHEK, 2009. – 278 p.11. Vozniyk G.V. Providing of innovative increase of economy of region by the effective use of financial potential of the real sector / G.V. Vozniyk. // Announcer of University of banking. – 2016. – №1. – P. 19-24.12. Sidenko V. Global structural transformations and trends of economy of Ukraine / V. Sidenko // Economy and prognostication. – 2018. – № 1. – P. 1-30.13. Lundval B.A. National Systems of Innovations – Towards a Teory of innovation and Interactive Learning / B.A. Lundval. – London: Pinter Publishers, 2016. – 315 p.Actual problems of international relations. Release 139. 201912614. Freeman C. The Economics of Industrial Innovation / by C. Freeman, L. Soete. – London and Washington: Pinter Publishers, 2017. – 570 p.15. Netson R. National Innovative Systems: Pre-conditions and Mechanisms of Functioning / R. Netson. – Lessonform Japan. L.: Printer, 2016. – 355 p.16. Efimenko T.I. Fiscal space of the антикризового adjusting / T.I. Efimenko. – К.: DNNU «Academy of financial management», 2012. – 332 p. 17. Eurostat (2018) Enterprises by type of innovation. Available at: http://appsso.eurostat.ec.europa.eu/nui/ submitView TableAction.do.18. Innovative Ukraine 2020: national lecture / by red. V. Geets and other; К.: NAN of Ukraine, 2015. – 336 p.

В статье исследуются объективные предпосылки и закономерности проведенння трансформационных изменений в экономике различных стран мира на инновационных принципах. Обоснованно, что развитие инновационной модернизации экономики должно быть одним из главных приоритетов системы государственного регулирования. Проанализирован опыт развитых стран мира относительно использования финансовых методов и инструментов для активизации инновационной деятельности и проведения НИОКР. Обоснованно, необходимость имплементации этого опыта в Украине для обеспечения модернизации экономики через использование различных налоговых льгот, ускоренной амортизации основного капитала, дешевых кредитов и т. п. Доказано, что разработка и реализация финансовых методов регулирования в механизме инновационной модернизации экономики должна учитывать особенности и структуру отечественной экономики, глубину глобализационных изменений и степень развития финансовых институтов. Направленность финансовых методов регулирования на проведение модернизации экономики предусматривает концентрацию, распределение и перераспределение финансово-экономических ресурсов, переориентацию экономики на инновационную модель развития. Определены приоритетные направления и разработаны рекомендации относительно совершенствования институциональных основ финансовой политики в условиях инновационной модернизации экономики Украины. Среди наиболее весомых направлений выделено: поиск новых источников и увеличение объемов финансирования инновационного развития, улучшения действенности влияния финансовых инструментов на темпы экономического роста, увеличение доли высокотехнологического сектора экономики и т. п.Ключевые слова: инновационная деятельность, финансовые методы регулирования, институциональное обеспечение, инновационная модернизация.

У статті досліджуються об'єктивні передумови та закономірності проведенння трансформаційних змін в економіці різних країн світу на інноваційних засадах. Обґрунтовано, що розвиток інноваційної модернізації економіки має бути одним із головних пріоритетів системи державного регулювання. Проаналізовано досвід розвинених країн світу щодо використання фінансових методів і інструментів для активізації інноваційної діяльності та проведення НДДКР. Обґрунтовано, необхідність імплементації цього досвіду в Україні для забезпечення модернізації економіки через запровадження різних податкових пільг, прискореної амортизації основного капіталу, дешевих кредитів тощо. Доведено, що розробка та реалізація фінансових методів регулювання в механізмі інноваційної модернізації економіки має враховувати особливості та структуру вітчизняної економіки, глибину глобалізаційних перетворень та ступінь розвитку фінансових інститутів. Спрямованість фінансових методів регулювання на проведення модернізації економіки передбачає концентрацію, розподіл та перерозподіл фінансово-економічних ресурсів, переорієнтацію економіки до інноваційної моделі розвитку. Визначено пріоритетні напрями та розроблено рекомендації щодо вдосконалення інституційних основ фінансової політики в умовах інноваційної модернізації економіки України. Серед найбільш вагомих напрямів виділено: пошук нових джерел та збільшення обсягів фінансування інноваційного розвитку, покращення дієвості впливу фінансових інструментів на темпи економічного зростання, збільшення частки високотехнологічного сектору економіки, тощо.Ключові слова: інноваційна діяльність, фінансові методи регулювання, інституціональне забезпечення, інноваційна модернізація.
ФИНАНСОВЫЕ МЕТОДЫ ВЛИЯНИЯ НА ИННОВАЦИОННУЮ МОДЕРНИЗАЦИЮ ЭКОНОМИКИ В КОНТЕКСТЕ МИРОВОГО ОПЫТА
ФІНАНСОВІ МЕТОДИ ВПЛИВУ НА ІННОВАЦІЙНУ МОДЕРНІЗАЦІЮ ЕКОНОМІКИ В КОНТЕКСТІ СВІТОВОГО ДОСВІДУ